THE FORMATION OF THE “PARLIAMENTARY INQUIRY” SYSTEM IN THE SENATE OF THE OF OLIY MAJLIS THE REPUBLIC OF UZBEKISTAN AND ITS ROLE IN PARLIAMENTARISM (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article reflects the formation and functioning of the parliamentary polling system in the Senate of the Oliy Majlis of the Republic of Uzbekistan. At the same time, the role of parliamentarism in its development was considered.